Teacher Enhancement Activities in the 4.0 Era - Punthasueb, Aimon; Intasingh, Somkiat; Nguenyuang, Sunee; Intanet, Nampueng (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
To develop the potential of students in the teaching profession to be potential teachers. Not only academic activities but also the curriculum development through teacher reinforcement activities is absolutely necessary. In accordance with the National Qualifications Framework for Higher Education 2009, institutions are required to set up teacher reinforcement activities each year. Which may organize activities / projects specifically or may be managed to integrate with learning in various courses. To strengthen the feature Being a teacher and citizenship not less than two activities per year. The teacher enhancement activities in the 4.0 era will have characteristics that can enhance the potential of teachers to become teachers in the 4.0 era with 3 characteristics, First the knowledge, knowledge in various areas such as teaching and learning. About oneself, students, communities, policies and education background, multicultural knowledge, assessing skills etc. Second is the skills, there are skills such as reflection and thinking skills, teaching skills, management skills communication skills, coordination skills, technology skills, innovation and entrepreneurial skills, questioning skills, evaluation skills and the environment that is conducive to learning skills, etc. Last one is the attitude. Teacher must have attitude that allow students to be a center of learning. Helping others and communities. Awareness of environmental changes. Social responsibility and team work.